LANGUAGE TEACHERS’ BELIEFS TOWARDS THE UPDATED CURRICULUM IN SECONDARY SCHOOLS OF KAZAKHSTAN - Askargali, Akerke (Nazarbayev University Graduate School of Education, 2022)
Six years ago, all the state schools of Kazakhstan experienced the update of a curriculum, which is moving away from a transmission of the knowledge paradigm, based on the criteria-based assessment, and views the student as a whole individual. The implementation of the updated curriculum was immediate, and many teachers found themselves having to adapt to the new circumstances. The beliefs and attitudes of language teachers towards the changes is under-researched and there is no data that informs to what extent their views have been taken into account before implementing the changes. This Master’s research aims at fulfilling this gap by interviewing teachers of Kazakh, Russian, and English languages. Teachers shared their experience of the updated curriculum, what they do to adapt and what they need to further improve their teaching practices. To shed light on these views Borg’s (2015) language teachers’ cognition framework has been used. It looks at three main components in teachers’ cognition: schooling, professional coursework, and classroom practice. The findings suggest that in the scope of the updated curriculum teachers’ schooling affects their teaching practices in that some of them still use the methods they were taught and keep practicing them in the new teaching program. Their professional coursework has altered their beliefs and practices of the updated curriculum, though not completely. Their classroom practices have changed and now they are proactive contemporary teachers who use criteria-based assessment as the main driver of their instruction. However, the Kazakh teacher complain that the borrowed topics and some methods of teaching do not fully reflect the local national values. Moreover, the trainings for the updated curriculum were not consistent in the pre-service and in-service. Lastly, most significantly, resource provision for rural regions is still insufficient. It is highly advisable that teachers’ voices are heard in the making of the educational system, and they take active participation in the curriculum development, along with content of their subjects. Moreover, their trainings must be not only on the new program in general but address the specificities of their subjects.
Keywords: Type of access: Open Access; language teachers beliefs; updated curriculum; teacher training; language teachers